UPSCALING BISNIS GULA SEMUT MELALUI SOSIALISASI KEAMANAN PANGAN DAN DIGITAL MARKETING - Winati, Famila Dwi; Fauziah, Emmareta; Zen, Bita Parga; Pratama, Aiza Yudha; Arifin, Miftahol (Jurnal AbdiMas Nusa Mandiri, 2025)
Palm sugar is the flagship product of Pernasidi Village, Banyumas Regency, which is managed in an integrated manner by KUB Merci. KUB Merci faces several obstacles in the production and management process, including a lack of knowledge about food safety and digital marketing, which results in suboptimal turnover. Traditional production methods also affect the cleanliness of the production kitchen, increasing the risk of contamination. This community service aims to improve participants’ understanding of Good Processed Food Processing (CPPOB) and digital literacy. The program is carried out through three stages: pre-service, implementation, and post-service, based on Participatory Rural Appraisal (PRA). The methods used include socialization and training, including material provision, hands-on practice, and discussion. The results of the program showed a significant increase in participants’ understanding of CPPOB (72%) and digital marketing (52%). In addition, the evaluation of participants’ satisfaction with the program showed positive results with an average score of 3.87. The long-term impact of this program is expected to improve the production standards and competitiveness of palm sugar products from Pernasidi Village through the sustainable application of CPPOB and digital marketing. The program is also expected to contribute to an increase in KUB Merci’s turnover and the economic welfare of the local community. However, a thorough implementation of CPPOB and intensive assistance in social media management is needed for the artisans to maximize marketing and expand market reach.